Abnormal Pulmonary Arterial Elastance Is Associated With Reduced Exercise Capacity in Tetralogy of Fallot. Issue 12 (18th June 2019) - Egbe, Alexander C.; Anavekar, Nandan S.; Connolly, Heidi M.
Abstract : Background: A previous study reported histologic abnormalities in the pulmonary artery (PA) of patients with tetralogy of Fallot (TOF). However, the potential effect of these anatomical findings on PA vascular function has not been studied. We hypothesized that TOF patients had abnormal PA vascular function, and that PA vascular function was associated with exercise capacity. Methods and Results: This a study of adult TOF patients who had cardiac magnetic resonance imaging and echocardiogram (on the same day) at Mayo Clinic, 2002–2015. In order to test the study hypothesis, we compared PA elastance index (PAEi) between 207 TOF patients and a referent group of 8 subjects without structural heart disease. PAEi was calculated as a quotient of PA systolic pressure and cardiac magnetic resonance imaging–derived right ventricular stroke volume. Mean age was 33±13 and 36±4 years in the TOF and referent groups respectively. TOF patients had higher PAEi compared with the referent group (0.62±0.12 versus 0.48±0.08 mm Hg/mL/m 2 ; P =0.001). There was a good correlation between PAEi and peak oxygen consumption (adjusted R 2 =0.73; r =0.85; P <0.001). After multivariate adjustment for potential confounders, PAEi was independently associated with peak oxygen consumption (adjusted R 2 =0.69; r =0.83; P <0.001). Conclusions: The high PA elastance in the TOF group may be attributed to abnormal PA vascular function. The association between PAEi and exercise intolerance suggests that PA vascular dysfunction may contribute to exercise intolerance, which is an important clinical problem in this population. Further studies are required to validate our findings and explore potential therapies to improve PA vascular function in this population.